PERLINDUNGAN KESEHATAN ANAK DARI BAHAYA COVID-19 MENURUT UNDANG-UNDANG KESEJAHTERAAN ANAK - Emir Dhia Isad; Wahyuni Retnowulandari (Reformasi Hukum Trisakti, 2022)
Children's rights to life and health are among the many things that the Covid-19 epidemic puts at jeopardy. Therefore, for children to thrive, effective cooperation from all sides is required. Particularly, Kramat Jati District, East Jakarta youngsters were included in the data area that the writers used as a sample. Formulation of the issue: How are parents, society, and the government working to protect children's health from the risks of Covid-19? In addition, are the efforts being made in line with the requirements of Law No. 4 of 1979 for Child Welfare? Descriptive, normative legal research is the approach used in this study. descriptive in character, qualitatively investigated, and deductive conclusions reached. The findings of the study, the analysis, and the conclusions demonstrate that the Covid-19 pandemic has negatively impacted children's growth and development in the medical field. It cannot be said that the community's role in child welfare, particularly in the health sector, or government policies related to upholding children's health rights during the Covid-19 Pandemic, which did not reach the layers public, are appropriate given that the majority of parents in the Kramat Jati District have been unable to fulfill their obligations to care for their children.